The hellenic kingdom and the ottoman Greeks: The experiment of the "society of Constantinople" - Veremis, Thanos (Δελτίο Κέντρου Μικρασιατικών Σπουδών, 1997)
[ Δε διατίθεται περίληψη / no abstract available]